The Undiscovered Country: Triumph, Tragedy, And The Shaping Of The American West : Triumph, Tragedy, And The Shaping Of The American West - Hutton, Paul Andrew, 1949- (New York, NY : Dutton, 2025)
"From the author of The Apache Wars, the true story of the American West, revealing how American ambition clashed with the realities of violence and exploitation The epic of the American West became a tale of progress, redemption, and glorious conquest that came to shape the identity of a new nation. Over time a darker story emerged-one of ghastly violence and environmental spoliation that stained this identity. The Undiscovered Country strips away the layers of myth to reveal the true story of this first epoch of American history. From the forests of Pennsylvania and Kentucky to the snow-crested California Sierras, and from the harsh deserts of the Southwest to the buffalo range of the Great Plains, Paul Andrew Hutton masterfully chronicles a story that defined America and its people. From Braddock's 1755 defeat to the 1890 Wounded Knee massacre, he unfolds a grand narrative steeped in romantic impulses and tragic consequences. Hutton uses seven main protagonists-Daniel Boone, Red Eagle, Davy Crockett, Mangas Coloradas, Kit Carson, Sitting Bull, and William "Buffalo Bill" Cody-as the biographical threads by which to weave a tapestry across seven generations, revealing a story of heroic conquest and dark tragedy, of sacrifice and greed, and of man-made wonders and environmental ruin. The American frontier movement has proven eternally fascinating around the world-the subject of countless books, paintings, poems, television shows, and films. The Undiscovered Country reveals the truth behind America's great creation myth"-- Provided by publisher.
Death on the Monongahela -- The forks of the Ohio -- Bushy Run -- Cumberland Gap -- The wilderness road -- The dark and bloody ground -- Kings Mountain -- The council fire -- The hearth -- Fort Mims -- The war of the Red Sticks -- The lion of the West -- The Texas -- The mountain men -- The Oregon Trail -- Manifest destiny -- California -- Lines on paper -- Flight of the ravens -- Land of the Jicarilla -- Valverde -- Mangas Coloradas -- Canyon de Chelly -- Adobe Walls -- The buffalo range -- Warbonnet Creek -- The dancing horse -- Wild West.
new book 2025 fall.
Includes bibliographical references and index
Keywords: History; Indigenous; West (U.S.) -- History